2017
DOI: 10.1111/bcpt.12652
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Melatonin Attenuates Isoflurane‐Induced Cognitive Impairment in Aged Rats through Hippocampal Melatonin Receptor 2 – cAMP Response Element Binding Signalling

Abstract: Melatonin exerts many physiological effects via melatonin receptors, among which the melatonin-2 receptor (MT ) plays a critical role in circadian rhythm disorders, Alzheimer's disease and other neurological disorders. A melatonin replacement strategy has been tested previously, and MT was a critical target during the process. cAMP response element binding (CREB) is an essential transcription factor for memory formation and could be involved in MT signalling. Therefore, the present study was designed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Melatonin is a potent antioxidant with no side effects even in the case of large-scale use. The neural injury models, such as cognitive impairment, exhibited neuroprotective effects (Liu Y. et al, 2013; Liu et al, 2017). Our experimental results also showed that melatonin reduces the cognitive impairment induced by isoflurane exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin is a potent antioxidant with no side effects even in the case of large-scale use. The neural injury models, such as cognitive impairment, exhibited neuroprotective effects (Liu Y. et al, 2013; Liu et al, 2017). Our experimental results also showed that melatonin reduces the cognitive impairment induced by isoflurane exposure.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2013; Zhang S. et al, 2016). A recent study showed that the level of melatonin in the hippocampus could be increased by the intraperitoneal injection of exogenous melatonin, thereby reducing the degree of cognitive dysfunction (Liu et al, 2017). However, the molecular mechanism of this effect is not yet clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is the main hormone produced by the pineal gland [ 1 ] and decreases with age in humans [ 2 , 3 ]. Melatonin also phosphorylates CREB, which is correlated with enhancements in learning and memory in mice and rats [ 4 , 5 ]. The phosphorylation of CREB by melatonin is likely mediated through the melatonin receptors, melatonin receptor 1 (MT1) and melatonin receptor 2 (MT2), according to a study of the nervous system [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of MT1 in SCN decreases with age, especially in AD [8,31,32]. Through normalizing the MT2, melatonin mediates phase advances in the SCN circadian clock of rats [33], and diminishes the isoflurane-induced cognitive impairment in aged rats [34]. The aforementioned reveals the importance of SCN, MT1, and MT2 on the normalization of the circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%